The CX3C-Chemokine Fractalkine in Kidney Diseases - Koziolek, M. J.; Vasko, R.; Bramlage, C.; Muller, G. A.; Strutz, F. (Mini Reviews in Medicinal Chemistry, 2009)
The chemokine CX3C-L/FKN is expressed in both soluble and transmembrane/mucin hybrid forms, thus combining chemoattractant functions together with receptor/adhesion molecule properties. In contrast to other chemokine receptors, CX3C-R is expressed not only on lymphoid cell populations, but also on several intrinsic cells including tubular epithelial cells and renal fibroblasts where it regulates various aspects of cell viability, matrix synthesis and degradation, migration, inflammation as well as oxidative stress. In the kidney, the chemokines/receptor pair has been shown to play a role in nephrogenesis as well as in the pathogenesis primary and secondary nephropathies. In several animal models and human specimens with acute and chronic renal failure including allograft nephropathy, CX3C-L/CX3C-R has been shown to exert immune and non-immune mediated renal damages. A blockade of this chemokine system ameliorated acute and chronic renal damages, though the latter to a more robust extent. There seems to a role of the CX3C-L/CX3C-R pair in mediating acute renal inflammation as well as in progressive chronic renal failure. However, functional studies are lacking for many aspects and further studies are necessary to better define the functional properties of CX3C-L/FKN and its receptor.
Keywords: nephrogenesis